Reciprocal effects of fibroblast growth factor receptor signaling on Dengue virus replication and virion production - Cortese, Mirko; Kumar, Anil; Matula, Petr; Kaderali, Lars; Erfle, Holger; Acosta, Eliana G.; Bühler, Sandra; Ruggieri, Alessia; Chatel-Chaix, Laurent; Rohr, Karl; Bartenschlager, Ralf (Cell reports, 2019)
Summary - Dengue virus (DENV) is a human arboviral pathogen accounting for 390 million infections every year. The available vaccine has limited efficacy, and DENV-specific drugs have not been generated. To better understand DENV-host cell interaction, we employed RNA interference-based screening of the human kinome and identified fibroblast growth factor receptor 4 (FGFR4) to control the DENV replication cycle. Pharmacological inhibition of FGFR exerts a reciprocal effect by reducing DENV RNA replication and promoting the production of infectious virus particles. Addressing the latter effect, we found that the FGFR signaling pathway modulates intracellular distribution of DENV particles in a PI3K-dependent manner. Upon FGFR inhibition, virions accumulate in the trans-Golgi network compartment, where they undergo enhanced maturation cleavage of the envelope protein precursor membrane (prM), rendering virus particles more infectious. This study reveals an unexpected reciprocal role of a cellular receptor tyrosine kinase regulating DENV RNA replication and the production of infectious virions.